Optimization of Digital Platforms as Part of SEO-Based Digital Marketing Strategy to Appear on Google: Optimasi Platform Digital sebagai Bagian dari Strategi Digital Marketing Berbasis SEO untuk Muncul di Google - Wijaya, Naufal Ariq; Ade Eviyanti (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze the benefits of utilizing five digital platforms, namely Pinterest, ISSUU, Tumblr,Flickr, and Carousell, to appear in Google search. This study uses a qualitative descriptive method with datacollection techniques through observation, analysis, and documentation. The results of the study show that eachdigital platform has different characteristics and functions in digital marketing. Digital platforms also have theirown advantages and disadvantages in increasing visibility and relevance in Google search. This study providesrecommendations for products or services that want to use digital platforms as part of their SEO-based digitalmarketing strategy.